Pulmonary MicroRNA Expression Profiling in an Immature Piglet Model of Cardiopulmonary Bypass‐Induced Acute Lung Injury. Issue 4 (27th October 2014) - Li, Wenlei; Ma, Kai; Zhang, Sen; Zhang, Hao; Liu, Jinping; Wang, Xu; Li, Shoujun
<x xml:space="preserve">Abstract</x> After surgery performed under cardiopulmonary bypass (CPB), severe lung injury often occurs in infants. MicroRNAs (miRNAs) are potentially involved in diverse pathophysiological processes via regulation of gene expression. The objective of this study was to investigate differentially expressed miRNAs and their potential target genes in immature piglet lungs in response to CPB. Fourteen piglets aged 18.6 ± 0.5 days were equally divided into two groups that underwent sham sternotomy or CPB. The duration of aortic cross‐clamping was 2 h, followed by 2 h reperfusion. Lung injury was evaluated by lung function indices, levels of cytokines, and histological changes. We applied miRNA microarray and quantitative real‐time polymerase chain reaction (qRT‐PCR) analysis to determine miRNA expression. Meanwhile, qRT‐PCR and enzyme‐linked immunosorbent assay were used for validation of predicted mRNA targets. The deterioration of lung function and histopathological changes revealed the piglets' lungs were greatly impaired due to CPB. The levels of tumor necrosis factor alpha, interleukin 6, and interleukin 10 increased in the lung tissue after CPB. Using miRNA microarray, statistically significant differences were found in the levels of 16 miRNAs in the CPB group. Up‐regulation of miR‐21 was verified by PCR. We also observed down‐regulation in the levels of miR‐127, miR‐145, and miR‐204, which were correlated with increases in the expression of the products of their potential target genes PIK3CG, PTGS2, ACE, and IL6R in the CPB group, suggesting a potential role for miRNA in the regulation of inflammatory response. Our results show that CPB induces severe lung injury and dynamic changes in miRNA expression in piglet lungs. Moreover, the changes in miRNA levels and target gene expression may provide a basis for understanding the pathogenesis of CPB‐induced injury to immature lungs.